STUDI LATAR BELAKANG PEMUDA PUTUS SEKOLAH DI KENAGARIAN LIMO KOTO KABUPATEN SIJUNJUNG - Refina Aisha; Khairani khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
The purpose this research are 1) to find out how the background that affects youth dropping out ofschool in Kenagarian Limo Koto, Sijunjung Regency 2) to find out how the role of parents in theeducation of their children in Kenagarian Limo Koto, Sijunjung Regency 3) parents and children canunderstand that education is very important. This type of research is descriptive qualitative. Researchinformants are 6 young people and their parents. This research was conducted by collecting data, reading and processing the data and then concluded. Data were collected through interviews anddocumentation. Based on the results of the study, it can be concluded that the reasons behind youthdropping out of school are social background, economic background and parents. A social backgroundwhere a bad environment has a huge impact on children's growth and development. From an economicpoint of view, the cost of education is not sufficient for schooling. And parents who are less concernedabout their children's education